Evaluating Post-Quantum Key Exchange Mechanisms for UAV Communication Security - Aissaoui, Ridwane; Deneuville, Jean-Christophe; Guerber, Christophe; Pirovano, Alain (IEEE/AIAA Digital Avionics Systems Conference, 2024)
The seamless integration of Unmanned Aerial Systems (UAS) into public airspace necessitates a robust UAV Traffic Management (UTM) system. Information security in communications plays a pivotal role in ensuring the operational safety of the UTM. Maintaining the integrity and authentication of unicast communications, such as command and video information, is imperative to thwart tampering and impersonation. Encryption emerges as an optimal solution for safeguarding such data. Efficient utilization of symmetrical encryption mandates the imple-mentation of secure key exchange mechanisms. However, intro-ducingAuthenticated Key Exchange (AKE) standards on diminutive Unmanned Aerial Vehicles (UAVs) encounters problems due to hardware limitations. To surmount this challenge, lightweight cryptographic algorithms tailored for resource-constrained hard-ware have been developed. Nonetheless, both lightweight and conventional cryptographic algorithms are susceptible to quantum computing threats. In response, post-quantum cryptographic primitives are undergoing standardization. This study assesses post-quantumKey Encapsulation Mechanism (KEM) candidates, namely CRYSTALS-Kyber, Hamming Quasi-Cyclic (HQC), and BIKE, on hardware resembling small UAVs. The evaluation of these algorithms focuses on computation time, considering real-time tasks during flights. The findings affirm the viability of employing unmodified standards on resource-constrained hardware concurrently with other priority tasks. Furthermore, quantum-vulnerable standards are also investigated to compare their performance against their more secure counterparts. All three post-quantum KEM candidates demonstrate usability in this environment, with CRYSTALS-Kyber being recommended for its superior performance, even surpassing certain prevailing standards.